Evaluación de la resistencia a la compresión en mezclas de mortero aplicando reemplazo del agregado fino por hueso porcino triturado siguiendo lo establecido en la normativa vigente colombiana (2022)
The department of Atlántico (Colombia) stands out for its pig production, so it is viable taking advantage of its derivatives. For this reason, with a background of sustainability, the present research analyzed the compressive strength of mortar cubes by replacing the fine aggregate with crushed pork bone, which was previously treated and cleaned, applying weight substitution percentages of 0%, 2%, 4 %, 6%, 8% and 10%, to identify the effect that this material generated in the mechanical and physical behavior of the samples. For the experimental development, 162 cubes were made, which were tested at 7, 14 and 28 days. The mortar design and the characterization of the materials was carried out in accordance with the Norma Técnica Colombiana, for which the following were considered: NTC 220, NTC 77, NTC 237, NTC 1776, NTC 92 and NTC 127. It was found that, at 28 days, the highest value of the average compressive strength obtained, to the cubes with bone replacement, was 2599 PSI with a 2% replacement and the lowest value of strength was 1095.22 PSI with a 10% replacement, recognizing that the 0% specimen achieved a strength of 4708.2 PSI; in this sense, it was detected that the resistance will be reduced with the increase of the percentage of replacement due to the presence of organic material in the crushed pork bone.